Clinicopathological differences between colonic and rectal carcinomas: are they based on the same mechanism of carcinogenesis?. Issue 6 (1st December 1999) - Konishi, K; Fujii, T; Boku, N; Kato, S; Koba, I; Ohtsu, A; Tajiri, H; Ochiai, A; Yoshida, S
Abstract : BACKGROUND: There is a difference in the location of colorectal mucosal lesions and invasive cancers. AIMS: To ascertain whether the location of colorectal neoplasms reflects the carcinogenesis pathway. METHODS: The subject material consisted of 4147 neoplastic lesions that had been resected endoscopically or surgically from 5025 patients. Mucosal lesions and submucosal cancers were classified into depressed and non-depressed types endoscopically or histologically. The relations between macroscopic type, size, histology, and location were investigated. RESULTS: ( a ) Non-depressed type. A total of 1774 of 3454 (51%) mucosal lesions were located in the right colon, 1212 (35%) in the left colon, and 468 (14%) in the rectum. The incidence of mucosal lesions larger than 10 mm was 10% (185/1774) in the right colon, 21% (254/1212) in the left colon, and 27% (127/468) in the rectum. The incidence of mucosal lesions with villous components was 2% (32/1774) in the right colon, 5% (63/1212) in the left colon, and 13% (62/468) in the rectum. The ratio of submucosal cancers to mucosal lesions was significantly higher in the rectum (0.064, 30/469) than in the left (0.034, 43/1279) or right (0.010, 18/1857) colon. ( b ) Depressed type. The incidences of depressed type mucosal lesions and submucosal cancers were 5% (83/1857) and 17% (3/18) in the right colon, 5% (67/1279) and 5% (2/43) in the left colon, and 0.2% (1/469) and 0% (0/30) in the rectum, respectively. CONCLUSION: There may be some mechanisms that promote the progression of mucosal lesions to invasive cancers in the left colon and rectum, whereas a de novo pathway from depressed type lesions may be implicated in some cancers of the right colon.